Representação sociocultural do conhecimento: contribuição teórico-metodológica para o campo informacional - Gaudêncio, Sale Mário (2020)
Contextually the thesis emerges in a scenario where the “excluded from knowledge” needs to be studied in the light of theories that aim at their inclusion and favor the places of speech. It is necessary to value an Emerging Paradigm, which enables an Ecology of Knowledge and which values the different forms of knowledge in the socio-cultural fields. In this sense, the thesis has the general objective of proposing a Knowledge Representation method in the light of the sociocultural paradigm of Information Science that can be able to organize and understand cybercordels, whose Digital Information Objects (ODI) are hybrid and volatile. It presents the following question as a problem: How to represent ODI as the strings in social media, while valuing its socio-cultural bias, its volatility and its hybridism? It proposes as a hypothesis that, based on a theoretical reframing and a combined method, it is possible to carry out the Sociocultural Knowledge Representation of ODI, hybrid and volatile, such as cybercordel. As a methodology, it shows the use of Scientific Bricolage, accompanied by the inclusion of Network Analysis in Social Media, Social Markers, Discursive Semantics and Dialectic of Knowledge. It brings as results what is called the Sociocultural Knowledge Representation Ecosystem (ERSC), anchored by principles to guide the replication of an ODI in the ERSC and a roadmap for the application of the Sociocultural Knowledge Representation (RSC) of ODI in the ERSC. The investigation finishes by concluding that the research was unprecedented as it reinterpreted the theory and combined methodologies in order to contribute and respond to new demands in the scientific field, allowing to present ways to treat ODI, considered volatile, as well as showing that there is an intimate interdisciplinary relationship between Knowledge Representation and the Sociology of Knowledge, Culture and Linguistics, placing them at the level of disciplines that can allow dialogue through Information Science and Sociology, favoring new and future researches around the Declassification of the Knowledge and the Decolonization of Knowledge.